2022
DOI: 10.3102/00028312221132533
|View full text |Cite
|
Sign up to set email alerts
|

Police Stops and School Engagement: Examining Cultural Socialization From Parents and Schools as Protective Factors Among African American Adolescents

Abstract: Police stops often perpetuate racial disparities in academic outcomes, yet few studies have examined factors that mitigate these negative consequences. Using two longitudinal studies (Study 1: n = 483, M-age = 12.88, 53% males; Study 2: n = 131, M-age = 15.11, 34% males), this article tests whether parental and school cultural socialization reduced the negative associations between police stops and youth’s school engagement. Results showed that youth with police encounters reported lower school engagement. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…30% and 42%). A lack of compensation in the fear of crime study may explain the difference in compliance with our study, however adolescents were compensated for participation in at least one of the Del Toro studies (25 USD, Del Toro and Wang, 2022). Compensation is an important technique to maintain participation, but other techniques such as gamification, reminders and feedback on compliance can work to minimise attrition as well (Dejonckheere and Erbas, 2021; Kronkvist and Engström, 2020; van Berkel and Kostakos, 2021; Wrzus and Neubauer, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…30% and 42%). A lack of compensation in the fear of crime study may explain the difference in compliance with our study, however adolescents were compensated for participation in at least one of the Del Toro studies (25 USD, Del Toro and Wang, 2022). Compensation is an important technique to maintain participation, but other techniques such as gamification, reminders and feedback on compliance can work to minimise attrition as well (Dejonckheere and Erbas, 2021; Kronkvist and Engström, 2020; van Berkel and Kostakos, 2021; Wrzus and Neubauer, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…The number of personal experiences was fairly low ( n = 27, 4%), but that is likely not unusual in the Dutch context where personal interactions with citizens are given relatively lower priority. To compare, a study of police contact among African American youth in the United States suggested that 9% of the sample reported being personally stopped by the police during a 14-day period (Del Toro and Wang, 2022). What this suggests is that some individuals may be more likely to get their information about police treatment and behaviour in daily life from media sources compared to personal encounters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations